The Grants, Concessions, and Original Constitutions of the Province of New-Jersey 103 (1752) - (:unkn) unknown (My University, 1675)
Be il enacfed by this Asiiemh\y, that no person or persons oi what state or degree soever within this Province, shall under any preetence sell, give or any other ways supply any Indian or Indians, with any guns or ammunituion whatsoever instrumental for war, or what quantity or worth soever, be it never so small...
Keywords: ENSLAVED PERSONS & OTHER MINORITIES